Ramona and her father - Cleary, Beverly; Dockray, Tracy (New York : HarperTrophy, 2006)
The family routine is upset during Ramona's year in second grade when her father unexpectedly loses his job.
Elem. School Library Collection.
Library Journal.
Newbery Medal/Honor.
Booklist, January 2005.
Elem. School Library Collection, March 1998.
Horn Book, March 2008.
Keywords: Dysfunctional families -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Family problems -- Fiction; Fathers and daughters -- Fiction; Family problems -- Fiction; Father-daughter relationship -- Fiction